Thick vs. Thin-Skinned : Technology, News, and Financial Market Reaction - Eichengreen, Barry; Lafarguette, Romain; Mehl, Arnaud (Washington, D.C. : International Monetary Fund, 2017)
We study the impact of technology on the reaction of financial markets to information, focusing on the foreign exchange market. We contrast the 'thin-skinned' view that technological improvements cause markets to react more to new information with the 'thick-skinned' view that they react less. We pinpoint exogenous technological changes using the timing of the connection of countries via the submarine fiber-optic cables used for electronic trading. Cable connections dampen the response of exchange rates to macroeconomic news, consistent with the 'thick-skinned' hypothesis. This is in line with the view that technology eases access to information and reduces trend-following behavior. According to our estimates, cable connections reduce the reaction of exchange rates to U.S. monetary policy news by 50 to 80 percent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet